Valve amplifiers - Jones, Morgan (Newnes, 2011)
Reviews of previous editions: Jam-packed with theory, circuit analysis, and DIY basics, it will walk you through all stages of design so that you can create your own wonders. Jones is an ex-BBC engineer with a cool writing style and you'll find it a no-pain education. Hi-Fi News and Record Review Valve Amplifiers is an extremely well written book, containing a wealth of information that all audio designers and builders will find useful. Glass Audio Valve Amplifiers is a market leader for one simple reason: in this specialist area it is recognized as the most complete guide to valve and vacuum tube amplifier design, modification, analysis, construction and maintenance. It is truly the all you need to know guide, and enables audio and circuit designers to succeed with their valve amplifier designs and projects. This book enables readers to understand, create, reconfigure and personalize high-end, audiophile quality amplifiers. Following a step-by-step approach to design, with little maths and lots of know-how, it starts with a brief review of electronic fundamentals relevant to valve amplifiers, simple stages, compound stages, linking stages together, and finally, complete designs. The new material included in this Fourth Edition ensures this book will stay at the top of any audio designer's or enthusiast's reference list. What's new: Chapter 1: Charge amplifiers Chapter 2: Additional circuits, semiconductor constant current sources expanded Chapter 3: Entire new section on noise Chapter 4: Lots of new measurements to explode or explain audio folklore Chapter 5: Astonishingly quiet, but cheap and simple HT supply Chapter 6: New power amplifier Chapter 7: New hybrid balanced RIAA stage, attenuator law faking VA3's focus was on distortion, but in VA4, focus is pushed towards background noise reduction. If that wasn't enough, there's more explanation, more measurements, more references, and plenty of new one-liners, any one of which might save hours of trouble. * The practical guide to analysis, modification, design, construction and maintenance of valve amplifiers * The fully up-to-date approach to valve electronics * Essential reading for audio designers and music and electronics enthusiasts alike.
Includes bibliographical references and index. - Print version
Keywords: Audio amplifiers